Numerical investigation of a friction test to determine the friction coefficients for the clinching process. (June 2022) - Bielak, Ch R; Böhnke, M; Bobbert, M; Meschut, G
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.